On the macroeconomic effects of reinvestments in asset purchase programmes - Rafael Gerke; Daniel Kienzler; Alexander Scheer (Deutsche Bundesbank, 2022)
A feature of recent monetary policy asset purchase programmes is the reinvestment policy: the central bank announces to keep the overall volume of assets on its balance sheet constant for some time. In this paper, we systematically assess the macroeconomic effects of such reinvestment policies. Conceptually, monetary policy can achieve a given macroeconomic stimulus by substituting higher overall volumes (more net purchases) with longer reinvestments. Quantitatively, we find that omitting reinvestments in a programme that embeds key features of the Eurosystem's pandemic emergency purchase programme reduces the effect on inflation by roughly one third. Stochastic simulations reveal that reinvestment policies can be applied to mitigate the constraints of upper purchase limits. Introducing bounded rationality attenuates the effects of reinvestment policies.
Keywords: D78; E31; E44; E52; E58; 330; Reinvestment; Stock effect; State-dependent asset purchases; Cognitive discounting; Bayesian estimation